THE EFFECT OF JOB STRAIN AND DEFENSE MECHANISMS ON BURNOUT OF HEALTH WORKERS WITH RESILIENCE AS AN INTERVENING VARIABLE (Study at Dr. Nur's Clinic, Cimahi City) - Feni Oktafiani; Sri Rochani Mulyani; Raden Ricky Agusiady T.S.; Ayu Laili Rahmiyati; Vip Paramarta; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Burnout is a psychological problem frequently experienced by healthcare workers due to high work demands, emotional stress, and patient care responsibilities. This study aims to analyze the influence of job strain and defense mechanisms on healthcare worker burnout, with resilience as an intervening variable at Dr. Nur Clinic in Cimahi City. This study used a quantitative approach with a survey method of healthcare workers working at Dr. Nur Clinic. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to test the relationship between the research variables. The results showed that job strain significantly influenced resilience, while defense mechanisms also had a significant influence on resilience. Resilience was shown to have a significant influence on healthcare worker burnout. Job strain did not directly influence burnout, while defense mechanisms had a significant effect on burnout. In addition, resilience was shown to mediate the relationship between job strain and defense mechanisms on burnout. The findings of this study indicate that burnout in healthcare workers is not only influenced by work pressure, but also by the individual's psychological ability to deal with work stress. Therefore, strengthening resilience and developing adaptive coping strategies are important to reduce the risk of burnout in healthcare workers.